Effects of Equal Volume But Different Plyometric Jump Training Intensities on Components of Physical Fitness in Physically Active Young Males. Issue 7 (July 2021) - Ramirez-Campillo, Rodrigo; Moran, Jason; Drury, Benjamin; Williams, Mark; Keogh, Justin W.; Chaabene, Helmi; Granacher, Urs
Abstract : Abstract: Ramirez-Campillo, R, Moran, J, Drury, B, Williams, M, Keogh, JW, Chaabene, H, and Granacher, U. Effects of equal volume but different plyometric jump training intensities on components of physical fitness in physically active young males. J Strength Cond Res 35(7): 1916–1923, 2021—An 8-week single-blind randomized controlled trial was conducted to compare the effects of separate programs of equal volume, but different intensity, plyometric jump training (PJT), on physical fitness in healthy adults. Thirty-eight physically active males (mean age: 21.8 ± 2.5 years) participated. Subjects were randomly assigned to one of 3 PJT groups or a control (CON, n = 9) according to their jump performance. Plyometric jump training was conducted at maximal (PJT-100, n = 10), high (PJT-80, n = 9), or moderate (PJT-65, n = 10) intensity within each group. Baseline and follow-up tests were performed for the assessment of countermovement jump (CMJ) height, CMJ height with arm swing (CMJA), and drop jump height from a 20-cm drop box (DJ20), linear speed (30 m), and change-of-direction speed (CODS) (the Illinois CODS test). Results revealed significant group × time interactions for CMJ, CMJA, DJ20, 30-m sprint, and CODS (all p < 0.001; d = 0.39–0.76). Post hoc analyses showed significant improvements in all 5 fitness measures for PJT-100 (all p < 0.01, Δ3.7–13.5%, d = 0.26–1.4). For PJT-80, 3 of 5 fitness tests demonstrated significant change (CMJ: p < 0.001, Δ5.9%, d = 0.33; CMJA: p < 0.001, Δ7.0%, d = 0.43; CODS: p < 0.001, Δ3.9%, d = 0.9), and for PJT-65, only 1 test was significant (CMJ: p < 0.05, Δ2.8%, d = 0.15). No significant changes were observed in CON. Except for similar gains in DJ20 and 30-m sprint in PJT-100 and PJT-80, gains in physical fitness were, in general, greater ( p < 0.05) after PJT-100 vs. PJT-80 vs. PJT-65 vs. CON. Therefore, maximal PJT intensity may induce larger physical fitness gains, although high and moderate intensities may also be useful, but to a lesser extent.